Development and experimental investigations of high power pulsed THz gyrotrons - Glyavin, M.; Luchinin, A.; Morozkin, M. (Радіофізика та електроніка, 2013)
The terahertz radiation looks promising for pointer plasma discharge, remote detection of concealed radioactive materials, plasma diagnostics based on collective Thompson scattering, enhancement of spectroscopy methods, new medical technology and so on. The aim of our investigations is development of powerful and relatively compact microwave sources. Powerful THz generation has been demonstrated in pulse gyrotrons. Pulsed coils with field intensity up to 50 T have been developed and tested. This field gives a chance to operate at fundamental cyclotron resonance conditions between electron beam and operating mode and, as result to simplify problem of mode selection. The output power 5 kW at 1 THz and 0.5 kW at 1.3 THz has been obtained with pulse duration 40 μs at the fundamental harmonic with 30 kV/5A electron beam. The power 200 kW at the frequency 0.67 THz has been realized with efficiency about 20 %. Despite the requirement of strong operating magnetic fields, the THz frequency has been achieved by the pulse gyrotrons operating at the fundamental harmonic. Today it is clear that relatively small-size tubes with a high level of output power (from a hundred to several kilowatts) at the frequencies of 0.3–1.5 THz will be available soon for many applications.